Turgor loss point and vulnerability to xylem embolism predict species‐specific risk of drought‐induced decline of urban trees. (27th October 2021) - Petruzzellis, F.; Tordoni, E.; Di Bonaventura, A.; Tomasella, M.; Natale, S.; Panepinto, F.; Bacaro, G.; Nardini, A.
ABSTRACT: Increasing frequency and severity of drought events is posing risks to trees' health, including those planted in urban settlements. Drought‐induced decline of urban trees negatively affects ecosystem services of urban green spaces and implies cost for maintenance and removal of plants. We aimed at identifying physiological traits that can explain and predict the species‐specific vulnerability to climate change in urban habitats. We assessed the relationships between long‐term risk of decline of different tree species in a medium‐sized town and their key indicators of drought stress tolerance, i.e . turgor loss point (TLP) and vulnerability to xylem embolism ( P 50 ). Starting from 2012, the study area experienced several summer seasons with positive anomalies of temperature and negative anomalies of precipitation. This trend was coupled with increasing percentages of urban trees showing signs of crown die‐back and mortality. The species‐specific risk of decline was higher for species with less negative TLP and P 50 values. The relationship between species‐specific risk of climate change‐induced decline of urban trees and key physiological indicators of drought tolerance confirms findings obtained in natural forests and highlights that TLP and P 50 are useful indicators for species selection for tree plantation in towns, to mitigate negative impacts of climate change. Abstract : The risk of decline and mortality of urban trees facing increased frequency/intensity of drought events was found to be correlated to species‐specific physiological traits, an in particular to their vulnerability to xylem embolism.